Android Based Educational Game Development to Improve Early Childhood Reading Ability - Nini Aryani; Rakimahwati Rakimahwati; Nisaul Hanifa (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research is motivated by the sophistication of technology to be developed in early childhood learning to improve children's reading skills. Reading is one of the skills retained by early childhood. The ability to read can facilitate children's learning at the subsequent level of education. This study aims to improve children's reading skills through android-based educational games. This study employs the type of research R D (Research and Development) with the ADDIE model, which refers to Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used a questionnaire. The results obtained from the development of children's reading skills through android-based educational games were declared valid, practical, and effective. The data collection instrument in this study was a questionnaire to test the validity, practicality, and effectiveness. The validation results of educational games were declared valid and very feasible to use with the means of Aiken's V by material experts was 0.89. The means of Aiken's V by media experts was 0.93. The Practicality of the Android-based Educational Game is highly feasible and has an average percentage result of 89%. The effectiveness is 91%. Therefore, educational games are declared effective. Hence, android-based educational games to improve children's reading skills in Raudhatul Atfhal are valid, practical, and effective.